A Comparative Analysis of Students’ Attitudes and Interests in Science Subjects - Zurweni, Zurweni; Azzahra, Miftahul Zannah (FKIP Universitas Lampung, 2021)
A Comparative Analysis of Students’ Attitudes and Interests in Science Subjects. Objective: This research was conducted with the aim of knowing the comparison of attitudes and interests and the relationship between students’ attitudes and interests towards science subjects with fermented material. Methods: This research uses quantitative methods with associative and comparative research types. Findings: the results of the T test with a value of sig. (2-tailed) < 0.05 and the results of the correlation test between attitudes and students’ interests in science subjects with fermented material obtained the results of the correlation test with the value of sig. (2-tailed) < 0.05. Conclusion: Based on the t-test there are differences in students’ attitudes and interests towards science subjects with fermentation material at SMPN 8 Batanghari and MTsN Batanghari 6. and MTsN 6 Batanghari Keywords: attitude, interest, fermentation, Biology, Science DOI: 10.23960/jpp.v11.i2.202112